2000
DOI: 10.1073/pnas.97.4.1601
|View full text |Cite
|
Sign up to set email alerts
|

Myeloblastin is a granulocyte colony-stimulating factor-responsive gene conferring factor-independent growth to hematopoietic cells

Abstract: Hematopoiesis depends on a pool of quiescent hematopoietic stem͞progenitor cells. When exposed to specific cytokines, a portion of these cells enters the cell cycle to generate an amplified progeny. Myeloblastin (MBN) initially was described as involved in proliferation of human leukemia cells. The granulocyte colonystimulating factor (G-CSF), which stimulates the proliferation of granulocytic precursors, up-regulates MBN expression. Here we show that constitutive overexpression of MBN confers factorindependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 46 publications
(35 reference statements)
2
35
1
1
Order By: Relevance
“…This cell line is a murine bone marrow-derived pro-B-cell line that depends on interleukin-3 (IL-3) for proliferation, but readily becomes IL3-independent in the presence of an oncogene or oncogenic event. Thus, the Ba/F3 cells represent a sensitive tool for measuring the effect of an introduced perturbation on cell proliferation and survival, not only for kinase genes but also non-kinase genes (Lutz et al 2000;Warmuth et al 2007;Yoda et al 2010;Cheung et al 2011).…”
Section: Novel Driver Cancer Genes In Endometrial Cancermentioning
confidence: 99%
“…This cell line is a murine bone marrow-derived pro-B-cell line that depends on interleukin-3 (IL-3) for proliferation, but readily becomes IL3-independent in the presence of an oncogene or oncogenic event. Thus, the Ba/F3 cells represent a sensitive tool for measuring the effect of an introduced perturbation on cell proliferation and survival, not only for kinase genes but also non-kinase genes (Lutz et al 2000;Warmuth et al 2007;Yoda et al 2010;Cheung et al 2011).…”
Section: Novel Driver Cancer Genes In Endometrial Cancermentioning
confidence: 99%
“…It is down-regulated during both normal myelopoiesis and the differentiation of human promyelocytic leukemia cell lines treated with different differentiation inducers (Bories et al, 1989;Labbaye et al, 1993;Zimber et al, 2000). Recently, it was demonstrated that the PR3 gene is a granulocyte colony-stimulating factor-responsive gene conferring factor-independent growth to hematopoietic cells (Lutz et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In another area of research focusing on myelopoietic mechanisms, PR3 (also termed myeloblastin) was described as a myeloid-specific serine protease (9). PR3 is expressed in human progenitor CD34 ϩ cells at the mRNA and protein levels and appears to be up-regulated by the granulocyte colonystimulating factor (G-CSF) (10).…”
mentioning
confidence: 99%